ANTIOXIDANT AND LIPID PEROXIDATION STATUS IN PRE AND POST OPERATIVE BREASTCARCINOMA - B.PRABASHEELA; DR.S.BASKARAN; ANUJ KUMAR SINGH (International Journal of Pharma and Bio Sciences, 2011)
Antioxidant enzymes considered as therapeutic agents for variety of disorders associated with oxidative stress. Serum Superoxide dis mutase, Catalase, Lipid peroxidation were quantified in 50 histopathologically proved Breast cancer patient in order to evaluate the changes in serum antioxidants status in pre and post breast carcinoma. When the data’s were compared with age matched healthy female, the level of antioxidant were found to decrease in patients with Breast cancer due to increased oxygen species. The levels of Catalase & Superoxide dis mutase was found to increase after surgery, showing improvement in treatment except few of the patients which showed no change in level indicating a chance of recurrence. The level of lipid peroxidation was significantly higher in Breast cancer patients and decreased after surgery. However further elaborate clinical studies are required to evaluate the role of such antioxidant enzymes in Breast cancer management.